Geochemistry of rare earth elements in a passive treatment system built for acid mine drainage remediation - Prudêncio, I. (2015)
Rare earth elements (REE) were used to assess attenuation processes in a passive system for acid mine drainage treatment (Jales, Portugal). Hydrochemical parameters and REE contents in water, soils and sed- iments were obtained along the treatment system, after summer and winter. A decrease of REE contents in the water resulting from the interaction with limestone after summer occurs; in the wetlands REE are significantly released by the soil particles to the water. After winter, a higher water dynamics favors the AMD treatment effectiveness and performance since REE contents decrease along the system; La and Ce are preferentially sequestered by ochre sludge but released to the water in the wetlands, influencing the REE pattern of the creek water. Thus, REE fractionation occurs in the passive treatment systems and can be used as tracer to follow up and understand the geochemical processes that promote the remediation of AMD.